A formação dos faxinais na Região Centro Sul do Paraná - Schuster, Wladimir Teixeira (2010)
On the Parana´s Center-south region exists a traditional agrosilvopastoril system called Faxinal System. This form of land use, on a general way, can be divided into two separated spaces: razing land and plantation land. Each one of the communities, even though they present this structure divided into two spaces, their internal characteristics are distinct. The present work aim to comprehend the economic insertion of the faxinais on a period that happened before their crisis and/or desegregation, this means, between the years 1920 and 1970. In fact, it is possible to notice that these communities came through periods when their economies were capable to provide to these social actors a better social reproduction way. leading to a better way of life. During that period, the faxinalenses communities had a regional economy, in other ways, ´territorialized´. It was common that the faxinalense´s profits coming from the selling of their products provided new land acquisition in which is an essential element for their survival. Besides, among the transformations that happened, when that local economy was ´desterritorialized´ or that regional market for the faxinalenses products came to an end, the crisis and desegregation became common on several faxinalenses communities. To a better comprehension of this question, it was elaborated an essay related to region concept, in which the main target was the faxinais region on its uncommon evolution’s consequences, when the social, economic, cultural and political factors shaped and distinguished them from the other regions in the State of Parana. For the comprehention of this social and territorial formation it became important the making of an essay that showed the several factors that influenced on the formation of this region, in which it was analyzed since the first colonization period, the several economic cycles and its contribution for the political, cultural, economic and social factors of this region.Besides, we tried to show the influence of the Federalist Revolution and the Contestado revolt. Another factor the contributed on the comprehension of the economic insertion of the communities was the use interviews among the old people (old people’s memories). From those people’s saying tied together to the IBGE Agricultural Census, it was possible a more precise comprehension of the economic insertion of these communities on that period.